The case for the use of telehealth for abortion in India. Issue 2 (10th January 2022) - Chandrasekaran, Sruthi; Chandrashekar, V. S.; Dalvie, Suchitra; Sinha, Anand
ABSTRACT: India has the world's fastest growing outbreak of COVID-19. With limited mobility, increased reports of intimate partner violence, changes in living patterns of migrants, delays in accessing contraception and safe abortion care, and potential changes to decisions about parenting, there may be an increased need for abortion services in India due to the pandemic. The use of technology for providing abortion information and services has been well documented in global literature. The safety of abortion provision using telehealth has been established in several contexts including the United States and Australia. The importance of hotlines and other support systems that use technology to provide information and support to clients through their abortion is also highlighted in the literature. Several countries, such as the United Kingdom, France, New Zealand, and Pakistan are now allowing the use of technology for abortion/post-abortion care in light of the pandemic; however, India's telemedicine guidelines do not include abortion. In a country where the majority of abortions take place outside the health system, allowing the use of telemedicine for abortion can help bring legality to users, and expand access to those facing additional barriers in accessing the care they deserve. We outline models for telemedicine provision of abortion in India and discuss the regulatory changes required to make telehealth for abortion a reality in India.